Overlaps of indigenous knowledge and climate change mitigation: evidence from a systematic review - Chanza, Nelson; Musakwa, Walter; Kelso, Clare (Frontiers in Climate, 2024)
There is now increasing acknowledgement of the role of indigenous and local people (ILP) in climate change, particularly in impact assessment, mitigation and adaptation. However, the methods and ways on how exactly indigenous and local knowledge (ILK) can be used in climate change action largely remain fragmented. While a growing share of scholarship has addressed the overlaps between ILK and adaptation, limited attention has been given on practical ways of working with indigenous communities to enhance knowledge of implementing mitigation actions. Without clearly articulated indigenous-sensitive methods for ILK integration in mitigation science, holders and users of this knowledge may remain at the boundaries of climate change action. Their knowledge and experiences may not be used to guide effective greenhouse gas (GHG) emission reduction activities. There are also fears that hurriedly and poorly developed mitigation projects that ignore indigenous and local communities may infringe their customary rights and livelihoods. To contribute to improved guidance on meaningful involvement of ILP in climate change mitigation, this study used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) to systematically review literature that links ILK and climate mitigation. We do this by (a) Identifying case studies that examine the overlaps of ILK and climate change mitigation from Scopus and Web of Science databases (n=43); (b) Analysing the methods used for engaging indigenous people in these studies; (c) Determining the knowledge, ways, practices and experiences of ILP that show mitigation benefits; and (d) Highlighting the direction for participatory engagement of ILP in mitigation research and practice. We have added to the emerging but fast growing knowledge on the overlaps of ILK and climate change mitigation. This intersection is evident in three ways: (a) validation and application of concepts used to understand carbon sequestration; (b) GHG emission reduction mainly from natural resource dependent livelihoods involving ILP; and (c) the application of participatory methodologies in research and the practice of climate change mitigation. We conclude that studies that focus on the intersection of ILK and climate mitigation need to use indigenous-sensitive methodologies to give more benefits for climate mitigation objectives while recognising the rights of ILP.